Anatomija pljuč - Čebašek, Vita (Medicinski razgledi, 2012)
Respiratory diseases are one of the major public health problems as they represent a significant cause of morbidity and mortality. Among more than 40 different respiratory diseases the highest global epidemiological bur den is associated with: upper and lower respiratory infections, asthma, chronic obstructive pulmonary disease, lung cancer and tuberculosis. The most important risk factors for respiratory diseases are tobacco, outdoor air pollution (particulate matter, ozone, nitrogen dioxide, sulphur dioxide), indoor air pollution in residential and working environments (different chemical substances, radon, asbestos), allergens and infectious agents. In terms of reducing the risk of respiratory diseases, it is crucial to limit the impact of risk factors on the population as much as possible. This can be achieved in two ways: by removing risk factor from the environment or by reducing the exposure of the population.
Keywords: bronchial tree; pljuča; pulmonary blood vessels; anatomija; pljučno žilje; bronchial blood vessels; bezgavke; lymph nodes; nerves; živci